Developing a Disaster Recovery Plan to Enhance Corporate Resilience and Ensure Business Continuity - Rohith Vallabhaneni; Vinod Veeramachaneni (Engineering And Technology Journal, 2024)
Disasters occur in the corporate operational environment. Earthquakes, floods, fires, and other unpredictable events that might disrupt company activities are among these calamities. The incidence of disasters in the workplace adds to unfavorable consequences. As a result, the construction of a disaster recovery plan becomes necessary for the firm to manage the bad consequences that may arise as a result of the unfavorable occurrences. With a disaster recovery strategy in place, a firm can sustain and swiftly restart normal operations. The firm's disaster recovery plan is a written document that outlines an efficient strategy for dealing with unforeseen and unmanageable catastrophes. Developing a disaster recovery strategy ensures the organization's survival by responding effectively to the present calamity.